Spine Registries: Where Do We Stand?. Issue 9 (November 2018) - Kaye, Ian D.; Butler, Joseph S.; Morrissey, Patrick B.; Sebastian, Arjun S.; Wagner, Scott C.; Vaccaro, Alexander R.
Abstract : To curb the unsustainable rise in health care costs, novel payment models are being explored which focus on value rather than volume. Underlying this reform is an accurate understanding of costs and outcomes. The Patient Protection and Affordable Care Act, the Institute of Medicine, and the Agency for Healthcare Research and Quality have specifically advocated for the use of registries to help define the real-world effectiveness of surgical interventions to help guide health care reform. Registries can help define value by documenting surgical efficacy, and specifically by reporting patient-based outcome measures. Over the past 10 years, several spine registries have been initiated and some others have expanded. These are providing a repository of evidence for surgical value. Herein, we will review the components of a well-designed registry and provide examples of such registries and their impact on health care delivery.